Իրակությունների թարգմանության մի քանի հարցեր - Անաիդա Մովսիսյան (ՀՀ ԳԱԱ հրատ.)
Реалии–это слова и словосочетания, которые имеют национальные и исторические оттенки значения, чуждые для других наций, и которыми называют вещи и истинности, характерные для жизни, образа жизни, социального или исторического прогресса определенной нации. The focal vocabulary consists of words and phrases that have national and historical shades of meaning. They are used to designate objects and realities typical of the lifestyle, of social or historical events of a certain nation or a group and these are foreign for other nations.
Keywords: Language and Literature; Translation and interpretation